A polyester composition, its preparation and use
Patent Information
- Application Number
- CN202512048374.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-31
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-12-31
AI Technical Summary
[0008]本发明的首要目的是克服目前技术中的可生物降解材料难以用作纸餐盒内覆膜的问题,提供一种聚酯组合物
本发明的聚酯组合物具有良好的耐热性,且该聚酯组合物做成的膜可以作为包装膜或包装袋,尤其适合作为纸餐盒的内覆膜,作为纸餐盒的内覆膜时,可以避免纸餐盒盛装热的食物时发生渗水和渗油现象。
Smart Images

Figure CN121628317B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biodegradable materials technology, and more specifically, to a polyester composition, its preparation method, and its application. Background Technology
[0002] Paper lunch boxes are lunch boxes made of paper. They are generally disposable paper lunch boxes, which are convenient to use and inexpensive, and have been widely used in the catering industry.
[0003] However, paper alone cannot be used directly as a lunch box because it is prone to water and oil seepage, making it unsuitable for holding food, especially juicy food. Furthermore, according to GB / T 27589-2011, paper lunch boxes should be designed to prevent water and oil seepage when holding hot food.
[0004] To ensure that paper lunch boxes meet usage requirements, an inner liner is typically laminated onto the inside of the paper lunch box substrate using a negative pressure heat lamination process. This inner liner serves to repel water and oil. Currently, the inner liner of paper lunch boxes is mainly polyethylene film. However, with the accelerated implementation of global plastic bans, it is necessary to find biodegradable materials to replace the currently difficult-to-biodegrade polyethylene film as the inner liner of paper lunch boxes.
[0005] Existing biodegradable films are difficult to use as inner linings for paper food containers due to insufficient water and oil repellency.
[0006] In addition, according to market research, the inner lining of paper food boxes also needs to withstand high temperatures to ensure that they can be used in scenarios such as heating (e.g., microwaving food), and the heat distortion temperature of existing biodegradable materials still needs to be improved.
[0007] Patent CN119529513 A, based on PLA (over 90%), with added starch for modification, significantly improves heat resistance, achieving non-adhesion and no melt marks at high temperatures. Patent CN 117063782 A constructs a PLA / PBS alloy, significantly improving heat resistance, increasing the Vicat softening temperature from 82℃ to 114℃. None of these patents mention its application as an inner lining for paper lunch boxes. Furthermore, all these patents use PLA as the base resin to construct the alloy; PLA is relatively brittle, limiting its application in the film and bag industry. Summary of the Invention
[0008] The primary objective of this invention is to overcome the problem that biodegradable materials are difficult to use as inner linings for paper food boxes in current technologies, and to provide a polyester composition.
[0009] A further object of the present invention is to provide a method for preparing the above-described polyester composition.
[0010] A further object of the present invention is to provide the use of the above-described polyester composition in the preparation of biodegradable membranes.
[0011] The above-mentioned objective of the present invention is achieved through the following technical solution: A polyester composition comprising the following components in parts by weight: 30-91 parts of aliphatic-aromatic copolyester Polylactic acid 5-51 parts, 8-15 parts of inorganic filler; The aliphatic-aromatic copolyester has a T content of 59~70 mol%, and the melt index measured at 190℃ and 2.16 kg is 1~10 g / 10 min; The polylactic acid is a copolymer of L-lactic acid and D-lactic acid, and the proportion of D-lactic acid repeating units is 1~16 mol%; The inorganic filler has a D50 particle size ≤ 7 μm.
[0012] It should be understood that the T content of the present invention refers to the ratio of the molar amount of aromatic dicarboxylic acid residues in the aliphatic-aromatic copolyester to the sum of the molar amounts of aromatic dicarboxylic acid residues and aliphatic dicarboxylic acid residues.
[0013] This invention regulates the melt index and T content of aliphatic-aromatic copolyester within a certain range, and adds inorganic fillers with a certain particle size range and a certain amount of polylactic acid with a specific D content (dextral lactic acid repeating unit content). This makes the polyester composition of this formulation system have a high Vicat softening temperature and good heat resistance. Furthermore, the polyester composition, when made into the inner lining of a paper lunch box, has good barrier properties and integrity, preventing water or oil leakage when the paper lunch box is filled with hot food.
[0014] If the T content of the aliphatic-aromatic copolyester is too low, the polyester composition of the present invention will have insufficient heat resistance, and oil seepage will occur after it is made into the inner lining of a paper lunch box.
[0015] If the melt index of the aliphatic-aromatic copolyester is too high, or the D content of the polylactic acid is too high, the heat resistance of the polyester composition of the present invention will be insufficient.
[0016] If the T content of the aliphatic-aromatic copolyester is too high, the melt index of the aliphatic-aromatic copolyester is too high, or the D content of polylactic acid is too high, or the ratio of aliphatic-aromatic copolyester to lactic acid is inappropriate, or the particle size of the inorganic filler is too large, it will be difficult for the polyester composition of the present invention to achieve both good barrier properties and integrity when the composite inner film is made, resulting in water and oil seepage after the polyester composition is made into the inner film of the paper lunch box.
[0017] It should be understood that the polyester composition of the present invention, when made into a film, can be used not only as an inner lining film for paper lunch boxes, but also as a common packaging film or packaging bag.
[0018] In this invention, aliphatic-aromatic copolyester is used as the main resin, and its content accounts for more than 30 wt% of the polyester composition.
[0019] In this invention, the amount of PBAT resin used can be 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, or 90 parts by weight, or a range formed by any two of the above values. The amount of polylactic acid used can be 5, 10, 15, 20, 25, 30, 35, 40, 45, or 50 parts by weight, or a range formed by any two of the above values. The amount of inorganic filler used can be 8, 10, 12, 13, or 15 parts by weight, or a range formed by any two of the above values.
[0020] In this invention, aliphatic-aromatic copolyester refers to a copolymer of aliphatic diacids and / or their ester derivatives, aromatic diacids and / or their ester derivatives, and diols.
[0021] In this invention, the aliphatic-aromatic copolyester can be commercially available or prepared in-house. The preparation method is as follows: an aliphatic diacid and / or its esterified derivative, an aromatic diacid and / or its esterified derivative, and a diol are mixed and reacted at 60-90 kPa and 180-235°C for 2.5-4 hours. A catalyst is added, and the mixture is then reacted at 230-260°C and 80-250 Pa for 6-12 hours to obtain the aliphatic-aromatic copolyester.
[0022] More preferably, the molar ratio of the aliphatic diacid and / or its esterified derivative to the aromatic diacid and / or its esterified derivative is 9~12:18~21.
[0023] More preferably, the ratio of the sum of the molar amounts of the aliphatic diacid and / or its esterified derivatives and the aromatic diacid and / or its esterified derivatives to the molar amount of the diol is 1:(1.05~1.3).
[0024] More preferably, the diol is at least one of butanediol or propylene glycol.
[0025] More preferably, a branching agent is added during the mixing process, including but not limited to glycerol.
[0026] More preferably, the molar ratio of the dicarboxylic acid to the branching agent is 1:(0.0003~0.002).
[0027] More preferably, the catalyst includes, but is not limited to, tetrabutyl titanate.
[0028] More preferably, the aliphatic dicarboxylic acid is C 4~12 At least one of the dicarboxylic acids.
[0029] Specifically, the C 4~12 The dicarboxylic acid is at least one of succinic acid, glutaric acid, adipic acid, pimelic acid, octanoic acid, azelaic acid, sebacic acid, undecanoic acid, or dodecanoic acid.
[0030] More preferably, the aromatic dicarboxylic acid is terephthalic acid.
[0031] Specifically, the aliphatic-aromatic copolyester can be at least one of polybutylene adipate terephthalate (PBAT) or polybutylene sebacate terephthalate (PBSeT).
[0032] In this invention, the T content of the aliphatic-aromatic copolyester can specifically be 59, 60, 62, 64, 65, 68, 69, or 70 mol%. The T content of the aliphatic-aromatic copolyester can be determined by nuclear magnetic resonance.
[0033] Preferably, the T content of the aliphatic-aromatic copolyester is 65~69 mol%. Controlling it within this range improves the heat resistance of the polyester composition.
[0034] In this invention, the melt index of the aliphatic-aromatic copolyester can specifically be 1, 2, 4, 5, 6, 8, or 10 g / 10 min. The melt index of the aliphatic-aromatic copolyester can be measured according to the ISO 1133-1:2022 standard.
[0035] Preferably, the melt index of the aliphatic-aromatic copolyester, measured at 190°C and 2.16 kg, is 1.3~5 g / 10 min. Controlling this range improves the heat resistance of the polyester composition.
[0036] Preferably, the aliphatic-aromatic copolyester has a melting point of 130~180℃. The melting point of the aliphatic-aromatic copolyester can be tested using DSC.
[0037] In this invention, polylactic acid can be either commercially available or prepared in-house. The in-house preparation method is as follows: polylactic acid is obtained by the ring-opening polymerization of lactide.
[0038] Preferably, the lactide includes L-lactide and meso-lactide.
[0039] More preferably, the mass ratio of L-lactide to meso-lactide is 68~98: 2~32.
[0040] More preferably, the ring-opening polymerization reaction is carried out in the presence of a catalyst, which includes, but is not limited to, stannous octoate.
[0041] More preferably, the ring-opening polymerization process is as follows: first, react at 130~145℃ and 1000~1400Pa for 3~5 hours, and then react at 160~180℃ and 300~500Pa for 5~8 hours.
[0042] In this invention, the melt index of polylactic acid (PLA) measured at 190°C and 2.16 kg can be 1, 2, 4, 5, 6, 8, or 10 g / 10 min. The melt index of PLA can be measured according to ISO 1133-1:2022 standard.
[0043] Preferably, the polylactic acid has a melt index of 1.2~5 g / 10 min measured at 190°C and 2.16 kg.
[0044] In this invention, the percentage of dextrorotatory lactic acid repeating units in polylactic acid can be 1, 2, 4, 5, 6, 8, 10, 12, 14, 15.5, or 16 mol%. The dextrorotatory lactic acid content of polylactic acid can be determined by gas chromatography.
[0045] Preferably, the inorganic filler is at least one of talc or calcium carbonate.
[0046] Preferably, the D50 particle size of the inorganic filler can be 1, 2, 3, 4, 5, 6 or 7 μm.
[0047] In this invention, the D50 particle size of the inorganic filler can be determined with reference to GB / T 19077.1-2008 "Particle Size Analysis by Laser Diffraction".
[0048] Preferably, the polyester composition further includes 0.1 to 2 parts of a compatibilizer.
[0049] More preferably, the compatibilizer is a copolymer containing epoxy groups, such as at least one of styrene-glycidyl methacrylate copolymer or ethylene-butyl acrylate-glycidyl methacrylate copolymer.
[0050] Preferably, the polyester composition further includes 0.1 to 2 parts of other auxiliaries.
[0051] More preferably, the other additives are at least one of antioxidants or lubricants.
[0052] More preferably, the antioxidant is at least one of hindered phenolic antioxidants or phosphite antioxidants.
[0053] More preferably, the lubricant is at least one of ethylene bis-stearamide, monoglyceride, oleamide, and erucamide.
[0054] The preparation method of the above polyester composition includes the following steps: mixing the components, melt extruding, and granulating to obtain the polyester composition.
[0055] Preferably, the temperature of the melt extrusion is 160~180℃; the screw length-to-diameter ratio of the extruder for the melt extrusion is 30~50:1, and the screw speed is 250~400rpm.
[0056] The application of the above-mentioned polyester composition in the preparation of biodegradable membranes is also within the scope of protection of this invention.
[0057] A film or bag is made from the above-described polyester composition.
[0058] The biodegradable film made from the polyester composition of the present invention can be used as a common packaging film or packaging bag in the art. In particular, the biodegradable film made from the polyester composition of the present invention can be used as an inner lining film for paper lunch boxes.
[0059] A coated paper includes a paper substrate and a film attached to the surface of the paper substrate, wherein the film is the aforementioned film.
[0060] Preferably, the coated paper is a paper lunch box or a lunch bag.
[0061] More preferably, the paper lunch box is a paper lunch box that can come into contact with hot food; the lunch bag is a lunch bag that can come into contact with hot food.
[0062] More preferably, the film is attached to the inner side of the paper substrate of the paper lunch box or to the inner side of the paper substrate of the lunch bag.
[0063] More preferably, the membrane is attached to the inner side of the paper lunch box substrate by a negative pressure heat coating process.
[0064] Compared with the prior art, the beneficial effects of the present invention are: The polyester composition of the present invention has good heat resistance, and the film made from the polyester composition can be used as a packaging film or packaging bag, especially suitable as an inner lining film for paper lunch boxes. When used as an inner lining film for paper lunch boxes, it can prevent water and oil leakage when the paper lunch box is filled with hot food. Attached Figure Description
[0065] Figure 1 The figure shows the experimental results of oil leakage from paper lunch boxes during a high-temperature oil resistance test. Detailed Implementation
[0066] To more clearly and completely describe the technical solution of the present invention, the present invention will be further described in detail below through specific embodiments. It should be understood that the specific embodiments described herein are only for explaining the present invention and are not intended to limit the present invention. Various changes can be made within the scope of the claims of the present invention.
[0067] The reagents used in the various embodiments and comparative examples of this invention are described below: I. Aliphatic-Aromatic Copolyester PBAT resin #1: Self-made, its preparation method is as follows: 19.5 mol of terephthalic acid, 10.5 mol of adipic acid, 32 mol of 1,4-butanediol, and 0.015 mol of glycerol were added to a reactor. The mixture was heated to 230°C (T1) and stirred for 3 hours (t1). During stirring, the pressure of the system was controlled at 70 kPa to remove the generated water. Then, 0.01% (by mass of the diacid and diol) of tetrabutyl titanate was added as a catalyst. The temperature was raised to 240°C (T2), a vacuum of 100 Pa was applied, and the reaction was carried out for 8 hours (t2) to obtain PBAT resin 1#. PBAT resin 1# has a melt index of 4.0 g / 10 min and a terephthalic acid content of 65 mol%.
[0068] PBAT Resin 2#: Self-made, its preparation method differs from PBAT Resin 1# in that it contains 18 mol of terephthalic acid and 12 mol of adipic acid. PBAT Resin 2# has a melt index of 3.9 g / 10 min and a terephthalic acid content of 60 mol%.
[0069] PBAT Resin 3#: Self-made, its preparation method differs from PBAT Resin 1# in that it contains 21 mol of terephthalic acid and 9 mol of adipic acid. PBAT Resin 3# has a melt index of 4.0 g / 10 min and a terephthalic acid content of 69 mol%.
[0070] PBAT Resin 4#: Self-made, its preparation method differs from PBAT Resin 1# in that time t1 is 4 hours and time t2 is 12 hours. PBAT Resin 4# has a melt index of 1.3 g / 10 min and a terephthalic acid content of 64 mol%.
[0071] PBAT Resin 5#: Self-made, its preparation method differs from PBAT Resin 1# in that time t1 is 2.5 hours and time t2 is 6 hours. PBAT Resin 5# has a melt index of 9.8 g / 10 min and a terephthalic acid content of 65 mol%.
[0072] PBAT Resin 6#: Self-made, its preparation method differs from PBAT Resin 1# in that it contains 17 mol of terephthalic acid and 13 mol of adipic acid. PBAT Resin 6# has a melt index of 4.0 g / 10 min and a terephthalic acid content of 57 mol%.
[0073] PBAT Resin 7#: Self-made, its preparation method differs from PBAT Resin 1# in that it contains 23 mol of terephthalic acid and 7 mol of adipic acid. PBAT Resin 7# has a melt index of 4.1 g / 10 min and a terephthalic acid content of 75 mol%.
[0074] PBAT Resin 8#: Self-made, its preparation method differs from PBAT Resin 1# in that time t1 is 2.5 hours and time t2 is 5 hours. PBAT Resin 8# has a melt index of 13.3 g / 10 min and a terephthalic acid content of 65 mol%.
[0075] In this invention, the T content of PBAT resin was determined by NMR. The specific process is as follows: 20 mg of PBAT resin sample was dissolved in 0.6 mL of deuterated chloroform, and then 1H NMR was measured at room temperature using a Bruker AV 500 NMR spectrometer, with the chloroform solvent peak located around 7.26 ppm. The four hydrogen atoms on the benzene ring in the repeating unit of terephthalic acid appeared around 8.10 ppm; the four hydrogen atoms in the two CH2 units adjacent to the carbonyl group in the repeating unit of adipic acid appeared around 2.33 ppm. Therefore, the molar content of terephthalic acid and adipic acid components can be expressed by the integrated areas (IT and IA) of the peaks at 8.10 ppm and 2.33 ppm. The molar content of terephthalic acid in PBAT resin (T content) = IT / (IT+IA)×100%.
[0076] In this invention, the melt index of PBAT resin was measured at 190°C and 2.16 kg.
[0077] In this invention, the melt flow index of PBAT resin can be measured by the ISO 1133-1:2022 standard.
[0078] II. Polylactic acid Polylactic acid 1#: Self-made, PLLA / PDLA copolymer, prepared as follows: 85 parts by weight of L-type lactide (purity ≥99.5%, the same below), 15 parts by weight of meso-lactide (purity ≥99.5%, the same below), lactide was dissolved in hexanediol, and stannous octoate (0.1 wt% relative to the total amount of lactide) was added for ring-opening polymerization. The reaction was first carried out at 138℃ and 1200 Pa for 4 hours (time t3), and then at 175℃ and 450 Pa for 6 hours (time t4). The product was then pelletized underwater, crystallized, and dried to obtain polylactic acid 1#. The melt index of polylactic acid 1# is 4.1 g / 10 min, and the dextrorotatory lactic acid content is 7.3%.
[0079] Polylactic acid 2#: self-made, its preparation method differs from that of polylactic acid 1# in that: the amount of L-type lactide is 98 parts by weight, and the amount of meso-lactide is 2 parts by weight. The melt index of polylactic acid 2# is 4.0 g / 10 min, and the content of dextrorotatory lactic acid is 1.1%.
[0080] Polylactic acid 3#: Self-made, its preparation method differs from that of polylactic acid 1# in that: the amount of L-lactide is 68 parts by weight, and the amount of meso-lactide is 32 parts by weight. The melt index of polylactic acid 3# is 3.9 g / 10 min, and the content of dextrorotatory lactic acid is 15.2%.
[0081] Polylactic acid 4#: Prepared in-house, its preparation method differs from that of polylactic acid 1# in that time t3 is 5 hours and time t4 is 8 hours. The melt index of polylactic acid 4# is 1.3 g / 10 min, and the content of dextrorotatory lactic acid is 7.5%.
[0082] Polylactic acid 5#: Prepared in-house, its preparation method differs from that of polylactic acid 1# in that time t3 is 3 hours and time t4 is 5 hours. The melt index of polylactic acid 5# is 9.9 g / 10 min, and the content of dextrorotatory lactic acid is 7.4%.
[0083] Polylactic acid 6#: In-house prepared, its preparation method differs from that of polylactic acid 1# in that the amount of L-lactide is 60 parts by weight and the amount of meso-lactide is 40 parts by weight. Polylactic acid 6# has a melt index of 3.9 g / 10 min and a dextro-lactic acid content of 20.4%.
[0084] In this invention, the dextrorotatory lactic acid (D-lactic acid) content of polylactic acid (PLA) can be determined by gas chromatography. The specific process is as follows: 100 mg of PLA sample is placed in a hydrothermal reactor, 10 ml of methanol is added, and 1 drop of NaOH aqueous solution is added. The hydrothermal reactor is then sealed. The hydrothermal reactor is placed in a 150°C forced-air oven for 60 min. After 60 min, the hydrothermal reactor is removed and cooled to room temperature by running water. The filtered sample solution is transferred to a gas chromatograph (Agilent 8860 gas chromatograph, CP7502 column). The peaks corresponding to D-lactic acid methyl ester and L-lactic acid methyl ester are determined based on the retention time, and the peak areas of D-lactic acid methyl ester and L-lactic acid methyl ester are recorded. The content of dextrorotatory lactic acid (D-lactic acid) in PLA is obtained by dividing the peak area of D-lactic acid methyl ester by the sum of the peak areas of D-lactic acid methyl ester and L-lactic acid methyl ester.
[0085] In this invention, the melt index of polylactic acid was measured at 190°C and 2.16 kg.
[0086] In this invention, the melt index of polylactic acid can be measured by the ISO 1133-1:2022 standard.
[0087] Inorganic filler #1: Talc, Imidas, HTPU, D50 is 2.1μm; Inorganic filler #2: Talc, Xinda, SDC-F7, D50 is 4.9μm; Inorganic filler #3: Talc, Xufeng, 1250N6, D50 is 9.3μm; Compatibilizer: Epoxy compatibilizer, BASF, ADR-4468; Other additives #1: Lubricant, monoglyceride, commercially available; Other additives #2: Antioxidant, Antioxidant 168, commercially available; Unless otherwise specified, all components (e.g., compatibilizer, other additive 1#, other additive 2#) selected in each parallel embodiment and comparative example are the same commercially available products.
[0088] The polyester compositions provided in the embodiments and comparative examples of the present invention were subjected to performance testing according to the following test methods: (1) Vicat softening temperature: Prepare a sample with a side length of 10 mm. During the test, place the sample horizontally under the unloaded indenter. The indenter should be at least 3 mm away from the edge of the sample. The sample surface in contact with the instrument should be flat. The load is 10 N and the heating rate is 50 °C / h. When the indenter is pressed into the depth of 1.00 mm, the instrument will automatically record the temperature at this time, which is the Vicat softening temperature (VST). Take the average value of 3 tests and record it.
[0089] (2) High-temperature oil resistance test: The inner film (40μm thick) made of polyester composition is laminated with the paper lunch box substrate (20cm*10cm*8cm) by negative pressure heat lamination process (heat lamination temperature is 180℃). Then, edible oil at 95℃ is poured into the lunch box and left to stand for 30 minutes. Then, observe whether the inner film seeps oil. If oil seepage occurs, Figure 1 The dark-colored oil stains shown indicate oil seepage, and the test result is unqualified, marked as NG; if there is no oil seepage, the test result is qualified, marked as OK.
[0090] (3) High temperature water resistance test: The inner film made of polyester composition (thickness of 40μm) is laminated with the paper lunch box substrate (20cm*10cm*8cm) by negative pressure heat lamination process (heat lamination temperature of 180℃). Then, 95℃ water is poured into the lunch box and left to stand for 30 minutes. Then observe whether the inner film is leaking water. If water seepage occurs (there are water seepage patches), the test result is unqualified and recorded as NG; if there is no water seepage, the test result is qualified and recorded as OK.
[0091] The polyester compositions of the embodiments and comparative examples of the present invention were prepared by the following method: Each component was weighed according to the formula, mixed evenly, and then fed into a twin-screw extruder for melt extrusion and granulation to obtain the polyester composition. The temperatures of the twin-screw extruder from zone one to zone ten were 160℃, 170℃, 170℃, 170℃, 170℃, 170℃, 170℃, 175℃, 175℃, and 175℃ respectively; the screw length-to-diameter ratio was 40:1; and the screw speed was 300 rpm.
[0092] Examples 1-12 Examples 1-12 provide a series of polyester compositions, the formulations of which are shown in Tables 1 and 2.
[0093] Table 1. Formulations (parts by weight) for Examples 1-7 .
[0094] Table 2. Formulations (parts by weight) for Examples 8-12 .
[0095] Comparative Examples 1-6 Comparative Examples 1-6 provide a series of polyester compositions, the formulations of which are shown in Table 3.
[0096] Table 3. Formulations (parts by weight) for Comparative Examples 1-6 .
[0097] The properties of the polyester compositions of each embodiment and comparative example were determined according to the test methods mentioned above, and the test results are shown in Table 4.
[0098] Table 4 Performance test results of polyester compositions in each example and comparative example .
[0099] As can be seen from Table 4: The Vicat softening temperature of the polyester compositions in Examples 1-12 is 96°C or higher, and no oil or water seepage was observed in the high-temperature oil resistance and high-temperature water resistance tests, indicating that the polyester compositions of the present invention have good heat resistance. Furthermore, when the polyester compositions are made into the inner lining of paper lunch boxes, water and oil seepage can be avoided when the paper lunch boxes are filled with hot food.
[0100] In Comparative Example 1, the T content of the added PBAT resin was too low, resulting in poor heat resistance of the polyester composition and substandard oil-blocking performance after being used as an inner liner for paper lunch boxes. In Comparative Example 2, the T content of the added PBAT resin was too high, resulting in substandard water and oil-blocking performance of the polyester composition after being used as an inner liner for paper lunch boxes. In Comparative Example 3, the melt index of the added PBAT resin was too high, resulting in poor heat resistance of the polyester composition and substandard water and oil-blocking performance after being used as an inner liner for paper lunch boxes. In Comparative Example 4, the D content of the added polylactic acid was too high, resulting in substandard water and oil-blocking performance of the polyester composition after being used as an inner liner for paper lunch boxes. In Comparative Example 5, the ratio of PBAT resin to polylactic acid was inappropriate, resulting in substandard water and oil-blocking performance of the polyester composition after being used as an inner liner for paper lunch boxes. In Comparative Example 6, the particle size of the added inorganic filler was too large, resulting in substandard water and oil-blocking performance of the polyester composition after being used as an inner liner for paper lunch boxes.
[0101] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.
Claims
1. A polyester composition, characterized in that, The components include the following parts by weight: 30-91 parts of aliphatic-aromatic copolyester Polylactic acid 5-51 parts, 8-15 parts of inorganic filler; The aliphatic-aromatic copolyester has a T content of 59-70 mol%, and a melt index of 1-10 g / 10 min measured at 190 °C and 2.16 kg. The aliphatic-aromatic copolyester is a copolymer of aliphatic diacids and / or their ester derivatives, aromatic diacids and / or their ester derivatives, and diols. The aromatic dicarboxylic acid is terephthalic acid; The aliphatic dicarboxylic acid is C. 4~12 At least one of the dicarboxylic acids, wherein the diol is at least one of butanediol or propylene glycol; The polylactic acid is a copolymer of L-lactic acid and D-lactic acid, and the proportion of D-lactic acid repeating units is 1~16 mol%; The inorganic filler is at least one of talc or calcium carbonate; The D50 particle size of the inorganic filler is 1~7 μm; The T content refers to the ratio of the molar amount of aromatic dicarboxylic acid residues in the aliphatic-aromatic copolyester to the sum of the molar amounts of aromatic dicarboxylic acid residues and aliphatic dicarboxylic acid residues.
2. The polyester composition according to claim 1, characterized in that, The aliphatic dicarboxylic acid is at least one of adipic acid or sebacic acid.
3. The polyester composition according to claim 1, characterized in that, The melt index of the polylactic acid measured at 190°C and 2.16 kg was 1~10 g / 10 min.
4. The polyester composition according to claim 1, characterized in that, The polyester composition further includes 0.1 to 2 parts of a compatibilizer.
5. The polyester composition according to claim 1, characterized in that, The polyester composition also includes 0.1 to 2 parts of other auxiliaries.
6. A method for preparing the polyester composition according to any one of claims 1 to 5, characterized in that, The process includes the following steps: mixing the components, melt extruding, and granulating to obtain the polyester composition.
7. Use of the polyester composition according to any one of claims 1 to 5 in the preparation of biodegradable membranes.
8. A film or bag, characterized in that, It is prepared by any of the polyester compositions according to claims 1 to 5.
9. A coated paper, characterized in that, It includes a paper substrate and a film attached to the surface of the paper substrate, wherein the film is the film of claim 8.
Citation Information
Patent Citations
Full-biodegradable edible fungus cultivation bag and preparation method thereof
CN117063782A
Biodegradable composite polylactic acid packaging bag and preparation method thereof
CN119529513A
Polylactic acid based composite material and preparation method and application thereof
CN105860462A
Polyester composition as well as preparation method and application thereof
CN119286204A